2002
DOI: 10.1046/j.1469-7580.2002.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

NADPH‐diaphorase distribution in the rabbit superior colliculus and co‐localization with calcium‐binding proteins

Abstract: Nitric oxide (NO) and calcium-binding proteins (CaBP) are important neuromodulators implicated in brain plasticity and brain disease. In addition, the mammalian superior colliculus (SC) has one of the highest concentrations of NO within the brain. The present study was designed to determine the distribution of nitric oxide-synthesizing neurons in the SC of the rabbit by enzyme histochemistry for reduced nicotinamide adenine dinucleotide phosphate-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In the superficial layers of the rat SC, all different cell types described with de Golgi technique (Langer and Lund, 1974) were shown to express nNOS (González-Hernández et al, 1992;Tenório et al, 1996;Soares-Mota et al, 2001), and the presence of the nNOS in these layers has also been reported in different mammalian species (González-Hernández et al, 1993;Egberongbe et al, 1994;Satoh et al, 1995;Tenório et al, 1995Tenório et al, , 1996Giraldi-Guimarães et al, 1999;Cork et al, 2000;Scheiner et al, 2001;González-Soriano et al, 2002). During development of the rat SC the first cells expressing nNOS were detected by the end of the first postnatal week.…”
Section: Introductionmentioning
confidence: 83%
“…In the superficial layers of the rat SC, all different cell types described with de Golgi technique (Langer and Lund, 1974) were shown to express nNOS (González-Hernández et al, 1992;Tenório et al, 1996;Soares-Mota et al, 2001), and the presence of the nNOS in these layers has also been reported in different mammalian species (González-Hernández et al, 1993;Egberongbe et al, 1994;Satoh et al, 1995;Tenório et al, 1995Tenório et al, , 1996Giraldi-Guimarães et al, 1999;Cork et al, 2000;Scheiner et al, 2001;González-Soriano et al, 2002). During development of the rat SC the first cells expressing nNOS were detected by the end of the first postnatal week.…”
Section: Introductionmentioning
confidence: 83%
“…Nitric oxide (NO) was recognized as the first gaseous neurotransmitter with a very short half-life time (2–6 s) (Greenwood and Earnshaw, 1997 ; Barañano et al, 2001 ; González-Soriano et al, 2002 ) and it has been implicated as a non-adrenergic non-cholinergic (NANC) inhibitory neurotransmitter at various sites in the nervous system (Grozdanovic et al, 1994 ; Schuman and Madison, 1994 ; Sharma et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…The activation occurs via interaction of NO with Fe +2 in the heme portion of the molecule, thereby altering its conformation and activating it, this causes conversion of guanosine triphosphate (GTP) to cyclic guanosine monophosphate (cGMP), which mediates many of the physiological actions of NO in mammalian cells (McCann et al, 2005 ). In aldehyde fixed tissue, nitric oxide synthase (NOS) is able to selectively catalyze a histochemically detectable Golgi-like dense staining of reactive neurons produced by Nicotinamide Adinine Dinulceotide Phosphate diaphorase (NADPH-d) histochemistry (González-Soriano et al, 2002 ). This is known as NADPH-diaphorase activity, which is used as a histochemical detection method for neuronal NO-producing structures (Bredt et al, 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of NOS-positive cells in the retinorecipient superficial layers of the superior colliculus has been reported in several mammalian species (19)(20)(21)(22)(23)(24)(25). In the rat, a subpopulation of all the different cell types described in the superficial layers of the superior colliculus by the Golgi technique (26) expresses nNOS (21,27,28).…”
Section: Introductionmentioning
confidence: 99%